True ternary fission in high energy proton reactions with 238U and 207Pb - Zamani, M.; Debeauvais, M. (HNPS Advances in Nuclear Physics, 2019)
A re-evaluation of ternary fission data collected in previous experiments of high energy proton reactions with 238U and 207Pb targets was made. The analysis of fragment mass distributions, fission fragment relative velocities and the kinetic energies of fragments permit to classify most of them as almost true ternary fission events. At the higher energies studied a percentage of 5% and about 2% for 238U and 207Pb respectively, present three equal masses and are events which belong to true ternary fission.